Strategi Pemasaran PT Bank Syariah Indonesia KCP Cemara Asri dalam Menawarkan Produk Pembiayaan Pra Pensiun Guna Menarik Minat Nasabah - Februari, Budi; Yanti, Nursantri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine effective marketing strategies in offering pre-pension financing products by PT Bank Syariah Indonesia KCP Cemara Asri and increasing customer interest in this product. This study also aims to determine how effective marketing strategies can increase bank income and improve the quality of Islamic financial services. In this study, researchers applied a qualitative method that prioritizes data collection through field study techniques or field research. This approach was chosen to obtain an in-depth understanding of the obstacles faced by Bank Syariah Indonesia KCP Cemara Asri in marketing pre-retirement financing products. Qualitative methods allow researchers to dive into the perspectives of various related parties and analyze effective marketing strategies to increase customer interest in these products. effective marketing strategies for PT Bank Syariah Indonesia KCP Cemara Asri for pre-retirement financing products involve an integrated and diverse approach. The steps include increasing public education about the product, strengthening digital promotion, establishing cooperation with companies, and organizing seminars and education to the public.